The complete mitochondrial genome of the rubber tree endophytic alga Heveochlorella hainangensis. Issue 2 (2nd April 2020) - Yu, Bohan; Ma, Shuai; Han, Bingying; Fu, Lili; Tan, Deguan; Sun, Xuepiao; Zhang, Jiaming
Abstract: Heveochlorella hainangensis is an endophytic green alga in the rubber tree. Its mitocondrion genome was sequenced and characterized. The complete mitogenome contains 54, 084 bp with a G + C content of 30.94%. It contains 56 genes, including 32 protein coding genes, 21 tRNA, and 3 rRNA genes. Phylogenetic analysis using the mitogenomes of Trebouxiophyceae species indicated that H. hainangensis is closely related to H. roystonensis, and they both clustered in the Watanabea clade.